Health literacy in the general population in the context of epidemic or pandemic coronavirus outbreak situations: Rapid scoping review. Issue 2 (February 2021) - Matterne, Uwe; Egger, Nina; Tempes, Jana; Tischer, Christina; Lander, Jonas; Dierks, Marie-Luise; Bitzer, Eva-Maria; Apfelbacher, Christian
Highlights: Health literacy (HL) is essential to control the pandemic. Should infection numbers surge again HL can help prevent the resumption of restrictions. We describe the extent of existing research on HL in the context of previous coronavirus outbreaks. Type of assessment of the domains of HL varied widely. Studies that examine interventions to improve pandemic related HL are needed. Abstract: Objective: The aim of this rapid scoping review, for which only studies from the general population were considered, was to describe the extent of existing research on HL in the context of previous coronavirus outbreaks (SARS-CoV-1, MERS-CoV and SARS-CoV-2). Methods: We searched major databases and included publications of quantitative and qualitative studies in English and German on any type of research on the functional, critical and communicative domains of HL conducted in the context of the three outbreaks in the general population. We extracted and tabulated relevant data and narratively reported where and when the study was conducted, the design and method used, and how HL was measured. Results: 72 studies were included. Three investigated HL or explicitly referred to the concept of HL, 14 were guided by health behaviour theory. We did not find any study designed to develop or psychometrically evaluate pandemic/epidemic HL instruments, or relate pandemic/epidemic or general HL to a pandemic/epidemic outcome, or any controlled intervention study. Type of assessment of the domains of HL varied widely. Conclusion: Theory-driven observational studies and interventions, examining whether pandemic-related HL can be improved are needed. Practice implications: The development and validation of instruments that measure pandemic-related HL is desirable.